Educational accountability in Brazil: meanings, challenges and criticisms (Research, Society and Development, 2022)
The article proposes to analyze how, from the 1980s onwards, the mechanisms of accountability in Brazilian basic education were forged, considering the emergence and strengthening of large-scale evaluations. It is characterized as a qualitative research, consisting of a literature review, of an exploratory and explanatory nature, with data collected from bibliographic and documentary research, but does not exhaust the production of the field. In order to understand the implementation of Brazilian public policy in the area of basic education, it is essential to understand how the federative pact is organized in the country, considering the functions attributed to the Union, states, Federal District and municipalities and how the idea of the State-evaluator and the managerial model that permeate the neoliberal ideology are assimilated and disseminated in the public administration. The creation, in Brazil, of large-scale assessment mechanisms dates back to the 1980s, with the Basic Education Evaluation System and based on changes made to the exam, so that it can support the creation of accountability mechanisms, implementing accountability policies, which start to populate the reality of Brazilian education systems and public schools. The creation of the Basic Education Development Index, in 2007, allowed the projection and monitoring of goals that are necessary to achieve the desired results and since then, large-scale evaluations have acquired prominence in educational policy, and various mechanisms of accountability are being created.